2013
DOI: 10.1002/qj.2190
|View full text |Cite
|
Sign up to set email alerts
|

Rossby wave‐breaking analysis of explosive cyclones in the Euro‐Atlantic sector

Abstract: The two-way relationship between Rossby wave-breaking (RWB) and intensification of extratropical cyclones is analysed over the Euro-Atlantic sector. In particular, the timing, intensity and location of cyclone development are related to RWB occurrences. For this purpose, two indices based on potential temperature are used to detect and classify anticyclonic and cyclonic RWB episodes from ERA-40 reanalysis data. Results show that explosive cyclogenesis over the North Atlantic (NA) is fostered by enhanced occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 81 publications
(102 reference statements)
3
66
0
Order By: Relevance
“…The definition of DWB adopted here is purposefully loose and inclusive, so as to provide a comprehensive overview of the phenomenon. More restrictive definitions such as that in Gómara et al [] requiring the RWB to exceed a minimum area threshold and to occur in specific geographical sectors have been tested, but it is found that they exclude a large number of events. Indeed, the discussion of DWB in Gómara et al [] focuses on an extremely limited number of cases (<1% of winter days).…”
Section: Geographical and Temporal Distribution Of Double Wave Breakingmentioning
confidence: 99%
“…The definition of DWB adopted here is purposefully loose and inclusive, so as to provide a comprehensive overview of the phenomenon. More restrictive definitions such as that in Gómara et al [] requiring the RWB to exceed a minimum area threshold and to occur in specific geographical sectors have been tested, but it is found that they exclude a large number of events. Indeed, the discussion of DWB in Gómara et al [] focuses on an extremely limited number of cases (<1% of winter days).…”
Section: Geographical and Temporal Distribution Of Double Wave Breakingmentioning
confidence: 99%
“…Pinto et al (2014) recently provided evidence that the occurrence of cyclone clusters is governed by a persistent, zonally orientated and extended eddy-driven polar jet stream over the eastern North Atlantic and Western Europe, which drives the North Atlantic cyclones towards the British Isles and sometimes further into Central Europe. The maintenance of these large-scale conditions is supported by two-sided Rossby wave breaking over the North Atlantic (Hanley and Caballero, 2012;Go´mara et al, 2014;Messori and Caballero, 2015). Pinto et al (2014) demonstrated for four selected stormy periods 1990, 1993, 1999 and 2007 that secondary cyclogenesis (new storms develop on the trailing fronts of previous storms, cf .…”
Section: Introductionmentioning
confidence: 98%
“…Variations in the UTLS jets influence influence surface weather patterns (e.g., see reviews by Lucas et al, 2014;Harnik et al, 2016) such as rainfall changes (e.g., Price et al, 1998;Raible et al, 2004;Karnauskas and Ummenhofer, 2014;Huang et al, 2015;Xie et al, 2015;Delworth and Zeng, 2014;Bai et al, 2016), destructive wind storms (e.g., Pinto et al, 2009Pinto et al, , 2014Gómara et al, 2014;Messori and Caballero, 2015), and extreme temperature events (e.g., Francis and Vavrus, 2012;Harnik et al, 2016). Moreover, transport processes that alter the extent and consequences of extratropical stratosphere-troposphere exchange (STE) are closely linked to the tropopause and jets, which are themselves sensitive to climate change and ozone depletion (e.g., Seidel and Randel, 2006;Lorenz and DeWeaver, 2007;Polvani et al, 2011;WMO, 2011;Hudson, 2012;Grise et al, 2013;Waugh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%